La table aux chiens (Kathakali) - Martinelli, Cedric; Touati, Julien (France, 2010)
Kathakali is a type of dance theatre from the Kerala region of India. The documentary provides insight into one of the last places where this form of theatre is taught. It documents the life of the students, following them to their classes, trainings, and doing their daily routine.
No dialogue
Verzio Film Festival Submission
Keywords: Documentary films